Integrated STEM-based Teaching Modules with the Values of Pancasila Student Profiles in Supporting the Implementation of Kurikulum Merdeka in Primary School - Fina Nur Oktaviah; Anik Dwiyanti; Suyadi; Mardyanto Barumbun (Jurnal Ilmiah Sekolah Dasar, 2023)
The presence of the Merdeka Curriculum as a new curriculum in Indonesia requires teachers to be able to adapt to these changes. On the other hand, there still needs to be more teacher references in implementing meaningful and character learning as aspired to through this new curriculum. Therefore, this development research aims to develop STEM-based teaching modules for 4th-grade elementary schools integrated with the Pancasila Student Profile. This type of research is developed using the ADDIE development model (Analyse, Design, Development, Implement, Evaluate). This research involved teachers and 50 grade 4 students in one of the public elementary schools in Indonesia. The modules were developed based on the needs of teachers and students obtained through observation, interviews, and diagnostic tests on students. Data analysis techniques using qualitative and quantitative descriptive analysis. The study's results, namely the validation of the experts on the module, showed a very good category for the material, display, and graphic aspects. The developed module is considered very practical for teachers in the classroom, while the student response to learning using the module is very good. It has a direct impact on student learning outcomes which are very satisfying. Thus, the developed module is feasible and can be an alternative reference for teachers in carrying out STEM-based learning by integrating the values of the Pancasila Student Profile.